A20 deletion in T cells modulates acute graft‐versus‐host disease in mice. Issue 11 (15th September 2017) - Fischer, Julius C.; Otten, Vera; Steiger, Katja; Schmickl, Martina; Slotta‐Huspenina, Julia; Beyaert, Rudi; van Loo, Geert; Peschel, Christian; Poeck, Hendrik; Haas, Tobias; Spoerl, Silvia
Abstract: The NF‐κB regulator A20 limits inflammation by providing negative feedback in myeloid cells and B cells. Functional lack of A20 has been linked to several inflammatory and autoimmune diseases. To define how A20 affects the functionality of T effector cells in a highly inflammatory environment, we performed conventional allogeneic hematopoietic stem cell transplantation (allo‐HSCT) with A20‐deficient CD4 + and CD8 + donor T cells in mice. Severity and mortality of graft‐versus‐host disease (GVHD) after allo‐HSCT was drastically reduced in recipients transplanted with conventional doses of A20‐deficient T cells. Consistently, we found that the A20‐deficient donor T‐cell compartment was strongly diminished at various timepoints after allo‐HSCT. However, proportionally more A20‐deficient donor T cells produced IFN‐γ and systemic inflammation was elevated early after allo‐HSCT. Consequently, increasing the dose of transplanted A20‐deficient T cells reversed the original phenotype and resulted in enhanced GVHD mortality compared to recipients that received A20 +/+ T cells. Still, A20‐deficient T cells, activated either through T cell receptor‐dependent or ‐independent mechanisms, were less viable than control A20 +/+ T cells, highlighting that A20 balances both, T‐cell activation and survival. Thus, our findings suggest that targeting A20 in T cells may allow to modulate T‐cell‐mediated inflammatory diseases like GVHD. Abstract : After allogeneic hematopoietic stem cell transplantation in mice, A20 −/− T cells display increased IFNγ production and higher rates of cell death compared to wild‐type T cells. Depending on the T‐cell dose, A20 −/− T cells can thus induce more GVHD early but less GVHD late after transplantation.